Decriminalizing Payment of Gamete Donors and Surrogates in Canada - Anne-Isabelle Cloutier (McMaster University Library Press, 2019)
On 29 May 2018, the Liberal MP Anthony Housefather tabled Bill C-404 titled An Act to amend the Assisted Human Reproduction Act which seeks to decriminalize the payment of gamete donors and surrogates across Canada. Although Prime Minister Justin Trudeau indicated the importance of having a societal debate on the subject, the bill was read only once by the House of Commons before it died on the Order Paper. Bill C-404 aimed to increase the number of Canadian gamete donors and surrogates to fulfill Canada's domestic needs, which are purportedly not being met because of a lack of economic incentives on the supply side and the existence of a grey market that deters some Canadians in acting as donors or surrogates and causes intending parents to fear being criminally sanctioned if the reimbursement they pay is deemed unrelated or unreasonable. While Bill C-404 has not been adopted by Parliament, this paper seeks to analyze the policy tensions at the heart of the decriminalization of payment of donors and surrogates-tensions that may well resurface in the future. As long as the alleged shortage of donors and surrogates persists, stakeholders are likely to continue to advocate for legislative change.  Le 29 mai 2018, le député libéral Anthony Housefather a déposé le projet de loi C-404 intitulé Loi modifiant la Loi sur la procréation assistée, qui vise à décriminaliser le paiement des donneurs de gamètes et des mères porteuses au Canada. Bien que le premier ministre Justin Trudeau ait souligné l'importance d'avoir un débat de société sur le sujet, le projet de loi n'a été lu qu'une seule fois par la Chambre des communes avant de mourir au feuilleton. Le projet de loi C-404 visait à augmenter le nombre de donneurs de gamètes et de mères porteuses pour répondre aux besoins intérieurs du Canada qui ne seraient pas satisfaits en raison du manque d'incitatifs économiques et de l'existence d'un marché gris qui dissuade certains Canadiens d'agir comme donneurs ou mères porteuses et qui fait en sorte que les parents craignent de possibles sanctions criminelles si le remboursement qu'ils offrent est jugé non-relié ou déraisonnable. Bien que le projet de loi C-404 n'ait pas été adopté par le Parlement, le présent document cherche à analyser les tensions politiques qui sont au coeur de la décriminalisation de la rémunération des donneurs et des mères porteuses-tensions qui pourraient bien réapparaître dans l'avenir, car la pénurie alléguée de donneurs et de mères porteuses est susceptible de persister et il est probable que les intervenants continueront à plaider pour un changement législatif.